2017
DOI: 10.1038/s41531-017-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and impact on quality of life of the pain modalities assessed by the King’s Parkinson’s disease pain scale

Abstract: In Parkinson’s disease, pain is a prevalent and complex symptom of diverse origin. King’s Parkinson’s disease pain scale, assesses different pain syndromes, thus allowing exploration of its differential prevalence and influence on the health-related quality of life of patients. Post hoc study 178 patients and 83 matched controls participating in the King’s Parkinson’s disease pain scale validation study were used. For determining the respective distribution, King’s Parkinson’s disease pain scale items and doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…In our study pain had an effect on quality of life, which was greater than motor impairment and comparable to the effect of motor complications. Other smaller studies have reported similar findings [24]. Given the amount of research that has gone into understanding mobility problems in PD, it is clear that there needs to be more research into understanding the causes of pain in PD with a view to developing improved treatments.…”
Section: Discussionmentioning
confidence: 66%
“…In our study pain had an effect on quality of life, which was greater than motor impairment and comparable to the effect of motor complications. Other smaller studies have reported similar findings [24]. Given the amount of research that has gone into understanding mobility problems in PD, it is clear that there needs to be more research into understanding the causes of pain in PD with a view to developing improved treatments.…”
Section: Discussionmentioning
confidence: 66%
“…These symptoms are frequently reported as one of the main sources of disease burden and impairment of quality of life in PD patients 30–32 . Pain is also a complex and common symptom in PD as seen in the PRIAMO study, 27 with a considerable impact on quality of life 33 . Specifically, musculoskeletal pain has been found to be highly prevalent in different studies, with abnormal nociceptive input processing in the central nervous system as a possible explicative factor 34,35 .…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, 35% of PD patients are affected by two types of pain, 10% by three, and 2% by four . Pain can become crippling in a subset of PD patients, affect their ability to conduct activities of daily living (ADL), and negatively impact their QoL . Despite the impact of this non‐motor symptom, pain often remains underdiagnosed and undeclared …”
Section: Introductionmentioning
confidence: 99%
“…14 Pain can become crippling in a subset of PD patients, affect their ability to conduct activities of daily living (ADL), 13,19 and negatively impact their QoL. [20][21][22] Despite the impact of this non-motor symptom, pain often remains underdiagnosed and undeclared. 23 PD patients with pain have been found to experience poorer sleep quality and more sleep disorders than patients without pain.…”
Section: Introductionmentioning
confidence: 99%